Differential gene expression and phenotypic variation across tissues between Saccharum officinarum and Saccharum spontaneum - Wang, Qin-Nan; Sun, Sheng-Ren; Chen, Jun-Lv; Zhou, Jing-Ru; Qin, Yuan-Xia; Zhang, Wei; Chen, Li-Yu; Gao, San-Ji (Frontiers in Plant Science, 2025)
Modern sugarcane cultivars (Saccharum spp.), predominantly derived from Saccharum officinarum and Saccharum spontaneum, exhibit divergent traits in sugar content, yield, and stress tolerance. However, little is known about the spatial transcriptional regulation pattern of the differentially expressed genes (DEGs) among tissues in the two Saccharum species. This study aimed to investigate these genes according to pathways in root, stem, leaf, and flower tissues using comparative transcriptome analysis. A broad range of DEGs, ranging from 24,469 to 34,198, were identified in four tissues from Badila (S. officinarum) and Ledong2 (S. spontaneum) clones. Thirty-one DEGs involved in abscisic acid (ABA) biosynthesis were identified in the root, suggesting differences in ABA content within root tissues between the two clones. In stem tissues, a significant number of upregulated DEGs were associated with cell growth and division, alongside plant-type cell wall organization, while abundant downregulated DEGs were linked to stress-response processes, possibly contributing to heterogeneity in stem morphology and stress responses. In leaf tissues, DEGs related to photosynthesis and photorespiration pathways likely influenced the variation in plant biomass and sucrose content between Badila and Ledong2. Key DEGs, including LHY, PRR7, and GI, associated with circadian rhythms and the photoperiodic pathway, were identified in flower tissues, providing evidence to explain the discrepancy in flowering time between the two clones. Collectively, the differential regulation of genes across four tissues may contribute to illustrating the divergence of agronomic traits and stress responses in both Saccharum species, offering a valuable foundation for the genetic improvement of sugarcane cultivation and stress resilience.